Use of PON and β2-M in the determination of renal and hepatic toxicity of sevoflurane - Yaşar, Demet; Yaşar, M. Akif; Erhan, Ömer L.; Özer, A. Belin; Demirel, İsmail; Toprak, Gonca Çağlar; Gülcü, Funda (Fırat University, 2006)
Objectives: We aimed to evaluate the effects of sevoflurane anesthesia on hepatic and renal functions. Materials and Methods: 40 patients with ASA I-II who undergone elective gynecologic operations that pass over 2 hours included into the study. Patients were devided into 2 groups randomly. The induction was applied with propofol, fentanyl and vecuronium in both groups, maintenance was carried out with sevoflurane in Group S and with propofol infusion in Group K. AST, ALT, total bilirubin, Hb, Hct, BUN, creatinine, PON 1, Lp(a), MDA levels in the blood and β2-M levels in the urine were evaluated just before the anesthesia induction, at 30 min. postoperatively and at 24 hours postoperatively. Mann Whitney-U, Wilcoxon Ranks Test and Pearson Correlation Analysis were used for statistical analysis. Results: Measuring within groups; ALT values increased significantly in Group S but there were no significant difference in AST and total bilirubine values. PON 1 values decreased significantly in Group S. There were no significant difference in Lp(a), BUN and creatinine values. β2-M values increased significantly in Group S, MDA values decreased significantly in Group K. Isochronal comparisons between groups; PON 1 values decreased significantly and β2-M values increased significantly in 24 hours measuring in Group S, MDA values decreased significantly in 24 hours measuring in Group K. Partial Correlation Analysis; Lp(a) with AST and ALT, β2-M with BUN and creatinine, PON 1 with AST and ALT values were statistically significant. Conclusion: With these data we concluded that sevoflurane can be used safely and PON 1, β2-M, Lp(a) and MDA levels can be used as new parameters at the evaluation of the hepatic and renal effects of sevoflurane among the routine measurings. ©2006, Fırat Üniversitesi, Tıp Fakültesi

Amaç: Sevofluran anestezisinin hepatik ve renal fonksiyonlar üzerine etkilerinin değerlendirilmesi amaçlanmıştır. Gereç ve Yöntem: ASA I-II grubundan iki saati aşan elektif jinekolojik operasyon planlanmış 40 hasta çalışmaya alındı. Hastalar randomize olarak iki gruba ayrıldı. Grup S ve Grup K’de; propofol, fentanil ve vekuronyum ile anestezi indüksiyonu yapılıp, Grup S’de sevofluran ile Grup K’de propofol infüzyonu ile anestezi idamesi sağlandı. Olguların anestezi indüksiyonundan hemen önce, postoperatif 30. dakika ve postoperatif 24. saatte, kanda AST, ALT, total bilirubin, Hb, Hct, KÜA, kreatinin, PON 1, Lp(a), MDA ve idrarda β2-M düzeyleri ölçüldü. Elde edilen verilerin istatistiksel değerlendirmeleri Mann Whitney-U, Wilcoxon Ranks Test ve Pearson Korelasyon Analizi uygulanarak yapıldı. Bulgular: Grup içi ölçümlerde; Grup S’de ALT değerleri anlamlı olarak artarken, AST ve total bilirubin ölçümlerinde anlamlı bir fark görülmedi. Grup S’de PON 1 değerlerinde anlamlı düşüş olurken, Lp(a), KÜA ve kreatinin değerlerinde anlamlı bir fark görülmedi. Grup S’de β2-M değerleri anlamlı olarak artarken, Grup K’de MDA ölçümlerinde anlamlı azalma görüldü. Eş zamanlı gruplar arası karşılaştırmalarda; Grup S’de 24. saat ölçümlerinde PON 1 değerlerinde anlamlı azalma , β2-M düzeylerinde anlamlı artış, Grup K’de 24. saat ölçümlerinde MDA düzeylerinde anlamlı azalma görüldü. Parsiyel Korelasyon Analizi’nde; Lp(a) ile AST ve ALT, β2-M ile KÜA ve kreatinin, PON 1 ile AST ve ALT değerleri istatistiksel olarak anlamlı bulundu. Sonuç: Sevofluranın güvenle kullanılabileceği ve sevofluranın hepatik ve renal etkilerinin değerlendirilmesinde PON 1 ve 2-M’nin rutin ölçümler arasında yeni parametreler olarak kullanılabileceği sonucuna varılmıştır. ©2006, Fırat Üniversitesi, Tıp Fakültesi
Sevofluranın Böbrek Ve Karaciğer Toksisitesinin Belirlenmesinde, Paraoksonaz Ve β2-Mikroglobulinin Yeri